The protective effect of Pentoxifylline on testopathy in male rats following Dimethyl Nitrosamine administration: An experimental study - Mohammad Reza Salahshoor; Azita Faramarzi; Shiva Roshankhah; Cyrus Jalili (Shahid Sadoughi University of Medical Sciences, 2019)
Background Nitrosamines as a carcinogenic agent has unfavorable effects on some of the male reproductive parameters. Pentoxifylline (PX) is a xanthine derivative used as a drug inhibiting the inflammatory factors, reducing blood viscosity, improving peripheral blood flow, and so on. Objective: The aim of the present study is to evaluate the effects of PX against Dimethyl nitrosamine (DMN)-inducing the damage to the reproductive parameter of male rats. Materials and Methods In this experimental study, 48 male Wistar rats (8 wk, 220-250 gr) were randomly assigned to eight groups (n = 6/each): normal control and DMN control groups (40 mg/kg); PX groups (25, 50, 100 mg/kg), and DMN + PX groups (25, 50, 100 mg/kg). Treatments were administered intraperitoneally and the gavage applied daily for 28 days. The sperm parameters, spermatogenesis index, total antioxidant capacity, testosterone level, and seminiferous tube diameter were assessed. Results The values of all parameters reduced significantly in the DMN control group compared to the normal control group (p < 0.001). The PX and PX + DMN treatments at all entirely doses improved all parameters significantly compared to the DMN control group (p < 0.001). Conclusion DMN caused detrimental effects on reproductive parameters. Also, no significant modifications were observed in PX treatments at all doses compared to the normal control group. PX compensated the toxic effect of DMN on reproductive parameters.